Tackifier-free hot melt adhesive composition, method of use thereof, and manufactured article using same

JP2023501786A5Active Publication Date: 2025-03-03BOSTIK INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2022525829
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2020-07-17
Filing Date
2020-10-28
Publication Date
2025-03-03
Estimated Expiration
2040-10-28

AI Technical Summary

Technical Problem

Existing hot melt adhesives for disposable hygiene products require high elongation to break, stress retention, and thermal stability, while avoiding the use of tackifiers to minimize odor and VOCs, and must handle superabsorbent polymers that swell significantly.

Method used

A tackifier-free hot melt adhesive composition comprising an amorphous single-site catalyzed high molecular weight propylene copolymer, a semi-crystalline single-site catalyzed low molecular weight propylene copolymer, and polyisobutene, which provides high elongation, stress retention, and excellent thermal stability.

Benefits of technology

The adhesive composition achieves high elongation at break (e.g., 350% or more), maintains stress retention (e.g., 30% or more after 10 minutes at 300% elongation), and exhibits excellent thermal stability (e.g., 90% viscosity retention after 3 days at elevated temperature).

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The tackifier-free hot melt adhesive composition preferably has a weight average molecular weight (M w Amorphous single-site catalyzed high molecular weight propylene copolymers having a M w The hot melt adhesive comprises a semi-crystalline, single-site catalyzed, low-molecular-weight propylene copolymer having a molecular weight of less than 60,000 g / mol; and polyisobutene. The composition may optionally contain a plasticizer, a butene-rich copolymer, and an antioxidant. The hot melt adhesive is particularly useful for bonding substrates that swell or elongate significantly during use. Such applications include bonding a superabsorbent polymer to a substrate or bonding two substrates together, at least one of which contains a superabsorbent polymer, such as a layer in the absorbent core of a disposable hygiene product such as a diaper. The tackifier-free composition demonstrates adequate elongation at break, stress retention, and thermal stability, making it well-suited for stabilizing swelling species such as superabsorbent polymers.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] FIELD OF THE INVENTION The present invention relates to a tackifier-free hot melt adhesive composition suitable for use in disposable hygiene articles such as diapers and training pants. The adhesive is particularly well suited for applications requiring high elongation at break, stress retention, and thermal stability. [Background technology]

[0002] Background of the Invention Hot melt adhesives typically exist as solid masses at ambient temperatures and can be converted to a flowable liquid by the application of heat. These adhesives are particularly useful in the manufacture of a variety of typically disposable products, often requiring the bonding of various substrates. Specific applications include disposable diapers, hospital pads, feminine sanitary napkins, panty shields, surgical drapes, and adult incontinence briefs, collectively known as disposable hygiene products or articles. Additionally, the adhesives can be used to manufacture preformed absorbent cores that are subsequently inserted into disposable or reusable products. Other diverse applications include paper products, packaging materials, automotive headliners, appliances, tapes, and labels. In most of these applications, the hot melt adhesive is heated to its molten state and then applied to a substrate, often referred to as the primary substrate. A second substrate, often referred to as the secondary substrate, is then immediately contacted and pressed onto the first substrate. The adhesive solidifies upon cooling to form a strong bond. A major advantage of hot melt adhesives is the absence of a liquid carrier that is present with water or solvent-based adhesives, thereby eliminating the costly steps associated with solvent removal as well as potentially harmful and / or odorous solvents.

[0003] For many applications, hot melt adhesives are often extruded directly onto a substrate in the form of a thin film or beads using piston or gear pump equipment. The die temperature must be maintained well above the adhesive's melting point to allow the molten hot melt material to flow smoothly through the application nozzle. Most applications involve the manufacture of food packaging and disposable nonwoven hygiene products, particularly those found in bonding delicate, heat-sensitive substrates such as thin-gauge plastic films. This imposes an upper limit on the coating temperature for hot melt adhesive application. Today's commercially available hot melts are typically formulated to have a coating temperature below 200°C to avoid burning or distorting the substrate. In this case, the adhesive is most typically sprayed from a nozzle at a set distance onto the target substrate or material, such as a substrate containing superabsorbent polymers. Several indirect or non-contact coating methods have also been developed that allow hot melt adhesives to be spray-applied onto a substrate from a fixed distance with the aid of compressed air. These non-contact coating techniques include conventional spiral spray, Signature™, Control Coat™, UFD™, and various forms of melt-blowing. However, indirect methods require that the adhesive viscosity be sufficiently low, typically in the range of 2,000-30,000 mPa s, and often in the range of 2,000-15,000 mPa s, to obtain an acceptable coating pattern.

[0004] Hot melt adhesives have traditionally been composed of polymers, plasticizers, tackifying resins (also referred to herein as "tackifiers"), and optional additives such as waxes and antioxidants. Tackifiers have long been considered a necessary component of hot melt adhesives. Traditionally, the role of tackifiers based on styrene block copolymers is to increase adhesion by raising the glass transition temperature of the adhesive system. Tackifiers also help control the viscosity of the final formulation. However, tackifiers can be viewed negatively because they can impart odor and volatile organic compounds (VOCs) to the adhesive formulation. Therefore, it is desirable to produce hot melt adhesives that do not contain tackifying resins. Polyolefin-based adhesives are desirable because such adhesives can handle high temperatures and are generally perceived to have less odor than other adhesives, such as styrene block copolymer-based adhesives.

[0005] Efforts have been made to develop tackifier-free hot melt adhesives. For example, U.S. Patent No. 9,139,755 discloses a hot melt adhesive composition comprising about 10 to 90% by weight of an amorphous polyolefin copolymer, about 50 to 70% by weight of 1-butene, about 10 to 90% by weight of a heterophasic polypropylene copolymer composition containing propene and a comonomer having amorphous properties and a crystalline block, including ethylene, 1-hexene, or 1-octene, and about 0.1 to 30% by weight of a polyisobutylene plasticizer prepared using AlCl3, wherein the adhesive provides cohesive strength from the heterophasic polypropylene copolymer and adhesive strength from the amorphous polyolefin copolymer.

[0006] Additionally, U.S. Patent No. 8,623,480 discloses a hot melt adhesive composition comprising at least 55% by weight of a first polymer consisting of a non-functionalized amorphous polyalphaolefin polymer containing more than about 50% by weight of polypropylene, a second polymer selected from the group consisting of polypropylene homopolymers, propylene copolymers, and combinations thereof, a functionalized polypropylene wax, and a polyethylene wax. The hot melt adhesive composition preferably does not contain a tackifier.

[0007] International Patent Application WO 2013 / 039261 discloses a hot melt adhesive composition comprising (A) a propylene homopolymer having a melting point of 100°C or less, obtained by polymerizing propylene using a metallocene catalyst, and (B) an ethylene-based copolymer. Summary of the Invention

[0008] There is a need in the art for adhesives that have low tack and sufficiently high elongation at break, stress retention, and thermal stability so that they can withstand significant swelling when wet, such as that of superabsorbent polymers, all the while having suitable viscosity at the desired application temperature.

[0009] Therefore, it would be advantageous to provide a hot melt adhesive that overcomes the drawbacks of the prior art adhesives described above. It is particularly desirable to produce a tackifier-free hot melt adhesive. Such adhesives are preferably polyolefin-based because they can handle high temperatures and are generally perceived as having less odor. Such adhesives have sufficiently high elongation at break and stress retention to withstand the swelling of superabsorbent polymers when wet or swollen / expanded. Such adhesives are particularly well-suited as microfiberizing adhesives, either alone or in combination with other adhesives and / or cellulose fibers, involved in incorporating superabsorbent polymers (SAPs) into sanitary articles such as diapers. Adhesives that perform this function are known to provide core stabilization. The adhesive does not need to have a high degree of tack, but is required to have very good elongation as it swells / expands to accommodate the inclusion of SAPs. The challenge in producing a tackifier-free adhesive is to develop a formulation with good thermal stability and sufficient "strength" to meet mechanical properties such as elongation at break and stress retention.

[0010] In view of the shortcomings of the prior art, the present invention provides a hot melt adhesive composition comprising an essentially amorphous, single-site catalyzed, high molecular weight propylene copolymer, a semi-crystalline, single-site catalyzed, low molecular weight propylene copolymer, and polyisobutene, the hot melt adhesive composition being tackifier-free. Such a composition provides both high elongation at break and stress retention while possessing excellent thermal stability.

[0011] According to one embodiment of the present invention, a method for producing a laminate comprises the steps of applying the hot melt adhesive composition of the present invention in a molten state to a primary substrate and bonding a secondary substrate to the primary substrate by contacting the secondary substrate with the adhesive composition.

[0012] According to another embodiment of the present invention, an absorbent core comprises a first layer and a second layer, at least one of the first layer and the second layer comprising a superabsorbent polymer, and the first layer and the second layer are adhered to one another by a hot melt adhesive composition of the present invention, which adhesive composition adheres the superabsorbent polymer within the absorbent core.

[0013] According to another embodiment of the present invention, a disposable sanitary article comprises an absorbent core of the present invention.

[0014] Detailed Description of the Invention According to one embodiment of the present invention, a hot melt adhesive composition comprises (a) an amorphous, single-site catalyzed, high molecular weight propylene copolymer, (b) a semi-crystalline, single-site catalyzed, low molecular weight propylene copolymer, and (c) polyisobutene, the composition being free of a tackifier. The adhesive composition optionally comprises antioxidant(s), optionally plasticizer(s), and a viscosity of 0.908 g / cm. 3 The adhesive may include an additional butene-rich polymer having a density less than 100%. Such compositions provide both high elongation at break and stress retention while possessing excellent thermal stability. Thus, such adhesives are particularly well suited for applications requiring the ability to elongate to a large extent during use (e.g., 350% or more), and provide high stress retention (e.g., 30% or more after 10 minutes at 300% elongation) and excellent thermal stability (e.g., 90% viscosity retained after 3 days at elevated temperature).

[0015] Both the first and second propylene copolymers used in the present invention are single-site catalyzed. Single-site catalyst systems (SSCs) differ from conventional catalysts (such as Ziegler-Natta catalysts) in at least one notable respect: they have only a single active transition metal site per catalyst molecule, and therefore, activity at this metal site is the same for all catalyst molecules. One type of SSC catalyst currently widely used on an industrial scale is a metallocene catalyst system consisting of a catalyst and a cocatalyst or activator. The catalyst is a transition metal complex with the metal atom located between two cyclic organic ligands, which can be the same or different derivatives of cyclopentadiene. The cocatalyst can be any compound capable of activating the metallocene catalyst by converting the metallocene complex into a catalytically active species. An example of such a compound is alumoxane, preferably methylalumoxane, having an average degree of oligomerization of 4 to 30. For purposes of the present invention, other neutral or ionic activators can be used, including, but not limited to, various organoboron compounds such as tri(n-butyl)ammonium tetrakis(pentafluorophenylborate), dimethylanilinium tetrakis(pentafluorophenylborate), or trityl tetrakis(pentafluorophenylborate). Another type of SSC catalyst is the constrained geometry catalyst (CGC).

[0016] As used herein, CGC refers to a subclass of SSC catalyst systems known as constrained geometry catalysts. Unlike metallocenes, constrained geometry catalysts (CGCs) are characterized by having only one cyclic ligand linked to one of the other ligands on the same metal center, such that the angle at this metal between the center of mass of the pi system and the additional ligand is smaller than in comparable unbridged complexes. More specifically, the term CGC is used for ansa-bridged cyclopentadienyl amide complexes, even though this definition extends far beyond this class of compounds. Thus, the term CGC is broadly used to refer to other ligand systems more or less related to the ansa-bridged cyclopentadienyl amide ligand system, which may or may not be isolobal and / or isoelectronic. Furthermore, the term is frequently used for related complexes with long ansa-bridges that do not induce strain.

[0017] Like metallocenes, suitable CGCs can be activated methylaluminoxane (MAO), perfluorinated boron, and trityl borate cocatalysts. However, catalyst systems based on CGCs exhibit higher alpha-olefin incorporation to a much greater extent than comparable metallocene-based systems. Nonmetallocene SSCs, also known as postmetallocenes, are also known as single-site catalysts for olefin polymerization. Typical postmetallocene catalysts are characterized by bulky, neutral alpha-diimine ligands. However, these postmetallocene catalysts are frequently used for the polymerization of ethylene to produce plastomers and elastomers. They are rarely used for the polymerization of alpha-olefins such as propylene. Single-site catalyst systems for olefin polymerization are well known to those skilled in the art and have been extensively discussed in two symposiums entitled Stereoselective Polymerization with Single-Site Catalysts (2008), edited by Lisa S. Baugh and Jo Ann M. Canich and published by CRC press, and Polyolefins: 50 Years after Ziegler and Natta II: Polyolefins by Metallocenes and Other Single-Site Catalysts (2013), edited by Walter Kaminsky and published by Springer Heidelberg.

[0018] The advances in SSC catalyst systems described above have made it practical to produce propylene-based polymers and copolymers with various chain microstructures and specific stereochemistry. Depending on the choice of catalyst and reaction conditions, specific types of propylene polymers and copolymers can be purposefully produced with, for example, narrow molecular weight distributions, statistically random comonomer incorporation, a high fraction of atactic chain sequences, and shorter, crystalline isotactic or syndiotactic chain sequences. Macroscopically, the polymers can exhibit relatively lower melting points, lower enthalpies of fusion, lower crystallinity, and lower densities, behaving more like elastomers than polypropylene produced with conventional catalysts. Such polymers may have various weight average molecular weight (Mw) ranges such as 1,000 g / mol to 1,000,000 g / mol, melting point ranges such as 20°C to 150°C, well below the melting point of iPP at 170°C, enthalpy of fusion ranges such as 0 J / g to 100 J / g, and density ranges such as 0.85 g / cc to 0.90 g / cc. Some of these polymers are well suited for hot melt adhesive applications.

[0019] Both the first and second propylene copolymers are composed primarily of propylene units, meaning that they contain at least 50% by weight of propylene. The two propylene copolymers can be polymers of propylene with the same or different comonomers. Preferably, the high molecular weight propylene copolymer is a polymer of propylene with ethylene and C4-C6 copolymers. 12 Similarly, low molecular weight propylene copolymers are copolymers of propylene with a comonomer selected from the group consisting of ethylene and C4-C6 alkylenes, preferably ethylene. 12 The first and second propylene copolymers are copolymers with a comonomer selected from the group consisting of alkylenes, preferably ethylene. The first and second propylene copolymers may have the same or different comonomer contents. Preferably, the first and second propylene copolymers have an ethylene content of about 5% to about 25%, more preferably about 7% to about 20%, even more preferably about 9% to about 17%, and most preferably about 10% to about 15%.

[0020] Preferably, the high molecular weight propylene copolymer has a weight average molecular weight of at least about 80,000 g / mole, preferably at least about 95,000 g / mole, and most preferably at least about 105,000 g / mole. Preferably, the weight average molecular weight of the high molecular weight propylene copolymer is at most about 250,000 g / mole, preferably at most about 200,000 g / mole, and most preferably at most about 175,000 g / mole. When upper and lower limits of a range of a component, adhesive, or other property or concentration are listed herein, any range extending from any lower limit to any upper limit is presumed to be contemplated by the invention, and any range extending from any lower limit or any range extending from any upper limit is also presumed to be contemplated by the invention. Thus, embodiments of the present invention include, by way of example, high molecular weight propylene copolymers having a weight average molecular weight of at least about 80,000 g / mol to at most about 250,000 g / mol, high molecular weight propylene copolymers having a weight average molecular weight of at least about 95,000 g / mol to at most about 250,000 g / mol, and high molecular weight propylene copolymers having a weight average molecular weight of at least about 80,000 g / mol. Preferably, the weight average molecular weight of the low molecular weight propylene copolymer is at most about 60,000 g / mol, preferably at most about 40,000 g / mol, and most preferably at most about 30,000 g / mol. Preferably, the weight average molecular weight of the low molecular weight propylene copolymer is at least about 10,000 g / mol, preferably at least about 15,000 g / mol, and most preferably at least about 17,500 g / mol. The weight average molecular weights of the two propylene copolymers described herein are characterized using high temperature size exclusion chromatography (SEC) using polypropylene reference standards.

[0021] Preferably, the molecular weights of the two propylene copolymers are significantly offset from one another, for example, in one embodiment of the present invention, the molecular weight of the high molecular weight propylene copolymer is at least two times, preferably at least three times, and most preferably at least four times the molecular weight of the low molecular weight polypropylene copolymer.

[0022] The polydispersity index (PDI) of the propylene copolymers may vary over a wide range and may be the same or different. The polydispersity index of the two propylene polymers is preferably at most about 5, preferably at most about 4, and most preferably at most about 3. The polydispersity index of the two propylene polymers is preferably at least about 1.5, preferably at least about 1.8, and most preferably at least about 2. These PDI values ​​are generally characteristic of polymers made using a single-site catalyst, such as a metallocene catalyst. Preferably, the propylene copolymers of the present invention are made using a metallocene catalyst. The polydispersity index (PDI) of the propylene copolymer is determined by dividing the weight average molecular weight by the number average molecular weight (M w / M n ) and M w and M n Each value of is determined using data from the same analytical method (i.e., using high temperature size exclusion chromatography (SEC) using a polypropylene reference standard).

[0023] The crystallinity of the two propylene copolymers has been found to be important for achieving certain objectives of the present invention. According to the present invention, the high molecular weight propylene copolymer is essentially amorphous, meaning that it has relatively low or no crystallinity. When viewing the crystallinity in terms of the heat of fusion of the polymer, the high molecular weight propylene copolymer preferably has a heat of fusion of at most about 20 J / g, preferably at most about 15 J / g, and most preferably at most about 10 J / g. Preferably, the high molecular weight propylene copolymer has a heat of fusion of at least about 0 J / g, preferably at least about 2 J / g, and most preferably at least about 5 J / g. According to an embodiment of the present invention, the low molecular weight propylene copolymer preferably has a heat of fusion of at least about 20 J / g, preferably at least about 25 J / g, and most preferably at least about 30 J / g. Preferably, the low molecular weight propylene copolymer has a heat of fusion of at most about 100 J / g, preferably at most about 75 J / g, and most preferably at least about 50 J / g. The test method used to determine these heat of fusion values ​​is ASTM E793-01 "Standard Test Method for Enthalpies of Fusion and Crystallization by Differential Scanning Calorimetry."

[0024] Preferably, the heats of fusion of the two propylene copolymers significantly cancel each other out, for example, in one embodiment of the present invention, the heat of fusion of the low molecular weight propylene copolymer is at least two times, preferably at least three times, and most preferably at least four times the heat of fusion of the high molecular weight polypropylene copolymer.

[0025] The melting temperatures, also referred to as melting points, of the two propylene copolymers may vary over a wide range and may be the same or different. Preferably, the melting temperature of the low molecular weight propylene copolymer is about 35°C to 100°C. More preferably, the melting temperature of the low molecular weight propylene copolymer is about 40°C to about 90°C, more preferably about 50°C to about 80°C, and most preferably about 55°C to about 75°C. Preferably, the melting temperature of the high molecular weight propylene copolymer is about 70°C to about 130°C. More preferably, the melting temperature of the high molecular weight propylene copolymer is about 75°C to about 125°C, even more preferably about 85°C to about 115°C, and most preferably about 90°C to about 110°C. The melting temperatures described herein are measured using a differential scanning calorimeter (DSC) according to ASTM E-794-01, with one change in the test being to use a scanning temperature of 20°C per minute instead of 10°C per minute.

[0026] The glass transition temperatures of the two propylene copolymers may vary over a wide range and may be the same or different. Preferably, the glass transition temperature of each copolymer is from about −45° C. to about −5° C. More preferably, the glass transition temperature is from −35° C. to −15° C., even more preferably from about −32° C. to −20° C., and most preferably from about −30° C. to −22° C. The glass transition temperatures described herein are measured using a differential scanning calorimeter (DSC) according to ASTM E-794-01, with one change in the test: a scanning temperature of 20° C. per minute instead of 10° C. per minute.

[0027] The melt flow rate of the high molecular weight propylene copolymer may vary over a wide range. The high molecular weight propylene copolymer may have a melt flow rate of about 1 g / 10 min to about 75 g / 10 min, preferably about 2 g / 10 min to about 50 g / 10 min, and most preferably about 5 g / 10 min to about 25 g / 10 min. The low molecular weight propylene copolymer may have a melt flow rate higher than that of the high molecular weight propylene copolymer, or the melt flow rate may be difficult to measure. In one embodiment of the present invention, a low molecular weight propylene copolymer is selected having a viscosity of about 500 cP to about 2,500 cP, preferably about 750 to about 2,000 cP, and most preferably about 1,000 to 1,500 cP, all at 190°C. As used herein, the melt flow rates of the two propylene copolymers are determined according to ASTM D 1238 using a 2.16 kilogram weight at 190°C.

[0028] Exemplary high molecular weight propylene copolymers suitable for use in the present invention include certain grades of VISTAMAXX™ propylene copolymers available from ExxonMobile, including VISTAMAXX 6202 and 6502, and certain grades of VERSIFY™ propylene copolymers available from Dow Chemical Company, including VERSIFY 3000. Exemplary low molecular weight propylene copolymers suitable for use in the present invention include certain grades of VISTAMAXX™ propylene copolymers available from ExxonMobile, including VISTAMAXX 8880.

[0029] In addition to the two propylene copolymers, the adhesive composition of the present invention includes polyisobutene. Herein, polyisobutene (PIB) refers to a homopolymer or oligomer made from isobutene monomer and containing repeating units of -[C(CH3)2CH2]-. These materials may or may not contain some degree of unsaturation. Generally, they have a low number average molecular weight (950-4,500 g / mol) and can be a thin or relatively viscous liquid at room temperature. According to embodiments of the present invention, the polyisobutene has a number average molecular weight of at least about 750 g / mol, preferably at least about 900 g / mol, more preferably at least about 1,500 g / mol, and most preferably at least about 2,000 g / mol. Preferably, the polyisobutene has a number average molecular weight of at most about 7,500 g / mol, preferably at most about 6,000 g / mol, and most preferably at most about 4,500 g / mol. They also typically possess a narrow polydispersity index (Mw / Mn<4), although this is not critical to the present invention. Exemplary polyisobutenes suitable for use in the present invention include INDOPOL® H-1900 or INDOPOL® H-100, available from Ineos Capital Ltd. Without being bound by any theory, it is believed that the polyisobutene helps to improve the cohesive strength of the adhesive and also helps to plasticize the propylene copolymer.

[0030] The hot melt adhesive composition of the present invention optionally includes a 1-butene copolymer. As used herein, the term "1-butene copolymer" means that the copolymer contains greater than 50 mole percent butene and is prepared from at least one other monomer in addition to butene. In one embodiment, the 1-butene copolymer selected may have a wide range of crystallinity (and a wide range of heat of fusion values). Preferably, the 1-butene copolymer includes a butene-ethylene copolymer. Generally, the weight average molecular weight of the 1-butene copolymer is preferably from about 15,000 to about 160,000 g / mol, and most preferably from about 30,000 to about 150,000 g / mol. As used herein, when referring to the weight average molecular weight of a 1-butene copolymer, the weight average molecular weight is determined by gel permeation chromatography using a polypropylene standard. Preferably, the 1-butene copolymer has a crystallinity of about 0.907 g / cm. 3 , preferably at most about 0.905 g / cm 3 , and more preferably at most about 0.900 g / cm 3 , and most preferably at most about 0.895 g / cm 3 It has a density of

[0031] The hot melt adhesive composition of the present invention optionally contains a plasticizer. The plasticizer may be any known compatible plasticizer, preferably selected from the group consisting of mineral oil and synthetic polyalphaolefin oil. Suitable plasticizers may also be selected from olefin oligomers and low molecular weight polymers, as well as vegetable and animal oils and their derivatives. Petroleum-derived oils that can be used are relatively high-boiling materials containing only small amounts of aromatic hydrocarbons. In this regard, aromatic hydrocarbons should preferably account for less than 30%, more particularly less than 15%, of the oil, as measured by the fraction of aromatic carbon atoms. More preferably, the oil may be essentially non-aromatic. The plasticizer useful in the present invention may be any number of different plasticizers, but mineral oils and other plasticizers having an average molecular weight of less than 5,000 daltons are particularly advantageous. As will be appreciated, plasticizers have typically been used to reduce the overall viscosity of the adhesive composition, extend the open time, and improve the flexibility of the adhesive without substantially reducing the adhesive strength and / or use temperature of the adhesive.

[0032] An embodiment of the present invention is an adhesive based on a mixture of high molecular weight propylene copolymer and low molecular weight propylene copolymer, where the ratio of high molecular weight propylene copolymer to low molecular weight propylene copolymer is from about 1:1 to about 5:1, preferably from about 3:2 to about 4:1, more preferably from about 2:1 to about 7:2, and most preferably about 3:1.

[0033] The amounts of the various components can vary over a wide range depending on the desired application temperature and other conditions of the adhesive and the desired performance characteristics. a high molecular weight propylene copolymer in an amount of about 10% to about 60%, preferably about 20% to about 50%, and most preferably about 25% to about 40% by weight based on the total weight of the composition; a low molecular weight propylene copolymer present in an amount of about 3% to about 40% by weight, preferably about 4% to about 30% by weight, and most preferably about 5% to about 20% by weight, based on the total weight of the composition; and Polyisobutene present in an amount of from about 5% to about 50% by weight, preferably from about 10% to about 40% by weight, and most preferably from about 15% to about 30% by weight, based on the total weight of the composition. Includes.

[0034] The present invention includes any combination of one component in any range with another component in any range or unlimited amount, or with both components. When present, the 1-butene copolymer may be present in an amount of about 5% to about 40% by weight, preferably about 7% to about 30% by weight, and most preferably about 10% to about 25% by weight, based on the total weight of the composition. Also, when present, the plasticizer may be present in an amount of about 5% to about 60% by weight, preferably about 10% to about 50% by weight, and most preferably about 15% to about 40% by weight, based on the total weight of the composition.

[0035] The present invention may optionally include an antioxidant, also known as a stabilizer. When included, the antioxidant may be present in an amount of about 0.1% to about 3% by weight of the total adhesive composition. Preferably, about 0.2% to 2% of antioxidant is incorporated into the composition. Antioxidants useful in the hot melt adhesive compositions of the present invention are incorporated to help protect the above-mentioned polymers, thereby protecting the overall adhesive system from the effects of thermal and oxidative degradation that typically occurs during adhesive manufacturing and application, as well as during normal exposure of the final product to the ambient environment. Among applicable antioxidants are high molecular weight hindered phenols and polyfunctional phenols, such as sulfur- and phosphorus-containing phenols. Hindered phenols are well known to those skilled in the art and can be characterized as phenolic compounds that also contain sterically bulky radicals in close proximity to their phenolic hydroxyl group. In particular, a tertiary butyl group is generally substituted on at least one benzene ring in the ortho position relative to the phenolic hydroxyl group. The presence of these sterically bulky substituted radicals in the vicinity of the hydroxyl group serves to retard its stretching frequency and, correspondingly, its reactivity; therefore, this steric hindrance provides phenolic compounds with their stabilizing properties.Representative hindered phenols include 1,3,5-trimethyl-2,4,6-tris(3-5-di-tert-butyl-4-hydroxybenzyl)benzene; pentaerythritol tetrakis-3(3,5-di-tert-butyl-4-hydroxyphenyl)propionate; n-octadecyl-3(3,5-di-tert-butyl-4-hydroxyphenyl)propionate; 4,4'-methylenebis(4-methyl-6-tert-butylphenol); 2,6-di-tert-butylphenol; 6-(4-hydroxyphenyl)-4,4'-methylenebis(4-methyl-6-tert-butylphenol); 2,3,6-tris(4-hydroxy-3,5-di-tert-butylphenoxy)-1,3,5-triazine; di-n-octadecyl-3,5-di-tert-butyl-4-hydroxybenzylphosphonate; 2-(n-octylthio)ethyl-3,5-di-tert-butyl-4-hydroxybenzoate; and sorbitol hexa-3(3,5-di-tert-butyl-4-hydroxyphenyl)propionate.

[0036] The performance of these antioxidants can be further enhanced by their use in combination with (1) synergists, such as thiodipropionates and phosphites; and (2) chelating agents and metal deactivators, such as ethylenediaminetetraacetic acid, its salts, and disalicylalpropylenediimine.

[0037] It should be understood that other auxiliary additives may be incorporated into the adhesive composition of the present invention to modify specific physical properties. These may include materials such as inert colorants (e.g., titanium dioxide), fillers, fluorescent agents, UV absorbers, surfactants, and other types of polymers. Typical fillers include talc, calcium carbonate, clay silica, mica, wollastonite, feldspar, aluminum silicate, alumina, alumina hydrate, glass microspheres, ceramic microspheres, thermoplastic microspheres, barite, and wood flour. Surfactants are particularly important for hygienic disposable nonwoven products because they can dramatically reduce the surface tension of the adhesive applied to the diaper core, thereby enabling more rapid transfer and subsequent absorption of urine by the core.

[0038] According to an embodiment of the present invention, a wax is included in the adhesive composition. Such waxes can include low molecular weight waxes, petroleum waxes such as paraffin wax, synthetic waxes, and polyolefin waxes. Preferably, the adhesive composition is substantially free of wax, e.g., containing less than 1 wt. % wax, more preferably less than 0.5 wt. % wax, based on the total weight of the composition, and most preferably free of wax.

[0039] According to an embodiment of the present invention, the hot melt adhesive composition consists essentially of or consists of an essentially amorphous single-site catalyzed high molecular weight propylene copolymer, a semi-crystalline single-site catalyzed low molecular weight propylene copolymer, and polyisobutene, and optionally a butene-rich copolymer, and optionally one or more other optional ingredients as described herein, and the adhesive is tackifier-free. "Tackifier-free" means that the composition does not contain a tackifier or contains only minimal amounts of tackifiers known in the art for use in hot melt adhesives, such as those disclosed in U.S. Patent No. 10,011,744, which is incorporated herein by reference. Classes of such tackifiers include aliphatic and alicyclic petroleum hydrocarbon resins; aromatic petroleum hydrocarbon resins and their hydrogenated derivatives; aliphatic / aromatic petroleum-derived hydrocarbon resins and their hydrogenated derivatives; aromatic-modified alicyclic resins and their hydrogenated derivatives; polyterpene resins having a softening point of about 10°C to about 140°C; copolymers and terpolymers of natural terpenes; natural and modified rosins; glycerol and pentaerythritol esters of natural and modified rosins; and phenol-modified terpene resins. According to one embodiment of the present invention, the adhesive composition does not contain amorphous polyalphaolefins. According to another embodiment of the present invention, the adhesive composition contains less than 40% by weight, preferably less than 25% by weight, more preferably less than 10% by weight, even more preferably less than 5% by weight, and most preferably less than 1% by weight of amorphous polyalphaolefins. According to another embodiment of the present invention, the adhesive composition does not contain styrene.

[0040] The flow characteristics and viscosity of the adhesive composition can be adjusted within certain parameters by methods known to those skilled in the art. The desired viscosity at a particular temperature will depend on the application conditions, including, among other factors, the mode of application, the desired flow during application, the line speed, and the system used in such application. According to an embodiment of the present invention, the viscosity of the composition is at most about 17,500 centipoise (cP) at about 177°C (350°F), preferably at most about 15,000 centipoise (cP) at 177°C (350°F), and most preferably at most about 12,500 centipoise (cP) at 177°C (350°F). According to an embodiment of the present invention, the viscosity of the composition is at least about 1,000 centipoise (cP) at 177° C. (350° F.), preferably at least about 2,500 centipoise (cP) at 177° C. (350° F.), and most preferably at least about 5,000 centipoise (cP) at 177° C. (350° F.). Adhesive viscosity is measured according to ASTM D3236 with spindle 27.

[0041] Adhesives according to embodiments of the present invention exhibit excellent mechanical properties (e.g., high elongation at break and high stress retention) and thermal stability. Such properties make them useful in hygiene, construction, and packaging applications, and are particularly well-suited for core stabilization of absorbent cores containing superabsorbent polymers that swell significantly upon sudden moisture ingress. The hot melt compositions of the present invention are further characterized by having an elongation at break of at least about 350%, preferably at least about 400%, more preferably at least about 450%, and most preferably at least about 475%, when measured at a pull rate of 2" / min. The formulations of the present invention further meet additional mechanical properties, such as a stress retained after 10 minutes at 300% elongation. Preferably, the stress retained after 10 minutes at 300% elongation is at least 30%, preferably at least about 40%, more preferably at least about 45%, and most preferably at least about 50%. In addition, the present invention Embodiments of the invention demonstrate excellent yield stress, such as at least about 0.4 MPa, preferably at least about 0.5 MPa, and most preferably at least about 0.6 MPa. The hot melt adhesive compositions further have excellent thermal stability, such that the viscosity retained at elevated temperatures is greater than about 85% for at least about 3 days, preferably greater than about 90% for at least about 3 days, and most preferably greater than about 90% for at least about 5 days. Methodologies for determining elongation at break, stress retention, yield stress, and thermal stability (as reflected by viscosity retention) are described in more detail in the Examples section below.

[0042] The hot melt adhesive composition of the present invention can be compounded using any mixing technique known in the art. A typical example of a mixing procedure involves placing all ingredients in a jacketed mixing kettle equipped with a rotor, then raising the temperature of the mixture to a range of 150°C to 200°C to melt the contents. Each component may be premixed or added individually to the mixing kettle. For example, the polymer may be a preformed mixture or blend, or may be added individually to the mixing kettle. It should be understood that the exact temperature used in this step will depend on the melting point of the specific components. Mixing is continued until a consistent, homogeneous mixture is formed. The contents of the kettle are protected with an inert gas, such as carbon dioxide or nitrogen, during the entire mixing process. Various additions and modifications can be made to the procedure for producing a hot melt composition without violating the spirit of the present invention, such as applying a vacuum to facilitate the removal of trapped air. Other equipment useful for compounding the compositions of the present invention include, but is not limited to, single- or twin-screw extruders or other variations of extrusion machines, kneaders, centralized mixers, Ross™ mixers, and the like. The hot melt adhesive is then cooled to room temperature and formed into chubs having a protective skin formed thereon or into pellets for shipping and use.

[0043] The adhesive composition of the present invention can be used as a general-purpose hot melt adhesive in many applications, such as disposable nonwoven hygiene products, paper converting, flexible packaging, wood processing, carton and case sealing, labeling, and other assembly applications. Particularly preferred applications include nonwoven disposable diaper and feminine sanitary napkin construction, reusable hygiene products incorporating preformed cores, elastic attachments for diapers and adult incontinence briefs, diaper and napkin core stabilization, diaper backsheet lamination, industrial filter material conversion, surgical gown and surgical drape assembly, etc. The composition of the present invention is particularly suitable for use in stabilizing absorbent cores containing superabsorbent polymers for disposable hygiene products such as diapers, feminine care pads, and adult incontinence products.

[0044] The resulting hot melt adhesive can be applied to a substrate using a variety of application techniques, including hot melt glue guns, hot melt slot die coating, hot melt wheel coating, hot melt roller coating, melt spray coating, spiral spray, contact or non-contact strand coating such as those branded Signature™, Control Coat™, UFD™, etc. In a preferred embodiment, the hot melt adhesive is indirectly sprayed onto the substrate.

[0045] In one embodiment of the present invention, a method of making a laminate includes the steps of (1) applying a hot melt adhesive composition of the present invention in a molten state to a primary substrate, and (2) contacting the secondary substrate with the adhesive composition, thereby bonding the secondary substrate to the primary substrate. In one embodiment of the present invention, the primary substrate comprises a first layer (such as a bottom layer) of an absorbent core, and the secondary substrate comprises a second layer (such as a top layer) of the absorbent core, with at least one of the first or second layers having a superabsorbent polymer bonded thereto. The primary and secondary substrates may be a single continuous material, or may be folded such that two folds form the primary and secondary substrates.

[0046] Any suitable absorbent core containing superabsorbent polymers can be used in connection with the present invention. Suitable absorbent cores are described in U.S. Patent Application Nos. 2017 / 0209616, 2017 / 0165133, and 2016 / 0270987, all of which are incorporated herein by reference. As described in U.S. Patent Application No. 2017 / 0165133, the absorbent core structure typically comprises an absorbent polymer material, such as a hydrogel-forming polymer material, also known as an absorbent gelling material (AGM), or a superabsorbent polymer (SAP). This absorbent polymer material ensures that a large amount of bodily fluid, such as urine, is absorbed and trapped by the absorbent article during use, providing low rewet and good skin dryness. Thinner absorbent core structures can be produced by reducing or eliminating the traditional use of cellulose or cellulose fibers in the absorbent core structure. To maintain the mechanical stability of these absorbent core structures, a fiberized network, which may optionally be an adhesive, may be added to stabilize the absorbent polymer material. The absorbent core may also have additional adhesive to supplement the fiberized network adhesive and / or to bond other core materials to each other and / or other article components. The superabsorbent polymer material may be deposited on or associated with the first and second substrates, with the fiberized network covering the superabsorbent polymer material on each of the first and second substrates.

[0047] In an embodiment of the present invention, the fiberized network comprises the adhesive composition of the present invention. The fiberized network may include other adhesives or other materials, such as cellulose fibers. In another embodiment of the present invention, the only adhesive used in the fiberized network is the adhesive composition of the present invention. In yet another embodiment of the present invention, the fiberized network consists solely of one or more adhesive compositions of the present invention. In one embodiment of the present invention, first and second absorbent layers are combined so that at least a portion of the fiberized network of the first absorbent layer is in contact with at least a portion of the fiberized network of the second absorbent layer, and the adhesive of the present invention used in the fiberized network serves to bond the two layers together to form the absorbent core. In an embodiment of the present invention, both the first and second layers of the absorbent core have a superabsorbent polymer bonded thereto. In another embodiment of the present invention, only one of these layers has a superabsorbent polymer bonded thereto.

[0048] In another embodiment of the method for manufacturing the laminate of the present invention, the primary substrate is the first layer of the absorbent core, and the secondary substrate is a superabsorbent polymer. The superabsorbent polymer may be deposited on the first layer before applying the adhesive composition. In this embodiment, the adhesive may form a fiberized network over and around the superabsorbent polymer and adhere to the first layer. In a further embodiment, a second layer is similarly formed, and then the two layers are joined to form the absorbent core before the adhesive is cooled.

[0049] Aspects of the present invention 1. (a) Essentially amorphous single-site catalyzed high molecular weight propylene copolymers; (b) a semi-crystalline single-site catalyzed low molecular weight propylene copolymer; and (c) polyisobutene; 1. A hot melt adhesive composition comprising:

[0050] 2. the high molecular weight propylene copolymer has a weight average molecular weight of at least about 80,000 g / mole, preferably at least about 95,000 g / mole, and most preferably at least about 105,000 g / mole, and a heat of fusion of at most about 20 J / g, preferably at most about 15 J / g, and most preferably at most about 10 J / g; and 2. The composition of embodiment 1, wherein the low molecular weight propylene copolymer has a weight average molecular weight of at most about 60,000 g / mole, preferably at most about 40,000 g / mole, and most preferably at most about 30,000 g / mole, and a heat of fusion of at least about 20 J / g, preferably at least about 25 J / g, and most preferably at least about 30 J / g.

[0051] 3. The high molecular weight propylene copolymer has a polydispersity index of less than about 5, preferably less than about 4, and most preferably less than about 3; and 3. The composition of any one of the preceding aspects, wherein the low molecular weight propylene copolymer has a polydispersity index of less than about 5, preferably less than about 4, and most preferably less than about 3.

[0052] 4. The high molecular weight propylene copolymer is a copolymer of propylene, ethylene and C4-C 12 copolymers with a comonomer selected from the group consisting of alkylene, preferably ethylene; and The low molecular weight propylene copolymer is a copolymer of propylene, ethylene and C4-C 12 Aspect 4. The composition of any one of aspects 1 to 3, wherein the composition is a copolymer with a comonomer selected from the group consisting of alkylene, preferably ethylene.

[0053] 5. The composition of any one of aspects 1-4, wherein the polyisobutene has a number average molecular weight of at least about 750 g / mol, preferably at least about 900 g / mol, more preferably at least about 1,500 g / mol, and most preferably at least about 2,000 g / mol.

[0054] 6. the high molecular weight propylene copolymer is present in an amount of from about 10% to about 60% by weight, preferably from about 20% to about 50% by weight, and most preferably from about 25% to about 40% by weight, based on the total weight of the composition; the low molecular weight propylene copolymer is present in an amount of from about 3% to about 40% by weight, preferably from about 4% to about 30% by weight, and most preferably from about 5% to about 20% by weight, based on the total weight of the composition; and Aspect 6. The composition of any one of aspects 1-5, wherein the polyisobutene is present in an amount of from about 5% to about 50% by weight, preferably from about 10% to about 40% by weight, and most preferably from about 15% to about 30% by weight, based on the total weight of the composition.

[0055] 7. The composition of any one of aspects 1 to 6, further comprising a polymer of a 1-butene-based copolymer.

[0056] 8. The composition of embodiment 7, wherein the 1-butene based copolymer comprises a butene-ethylene copolymer.

[0057] 9. The 1-butene copolymer has a viscosity of up to about 0.907 g / cm 3 , preferably at most about 0.905 g / cm 3 , and more preferably at most about 0.900 g / cm 3 , and most preferably at most about 0.895 g / cm 3 9. The composition of any of embodiments 7 or 8, having a density of

[0058] 10. The composition of any one of aspects 7-9, wherein the 1-butene copolymer is present in an amount of about 5% to about 40% by weight, preferably about 7% to about 30% by weight, and most preferably about 10% to about 25% by weight, based on the total weight of the composition.

[0059] 11. The composition of any one of aspects 1-10, further comprising a plasticizer.

[0060] 12. The composition of aspect 11, wherein the plasticizer is selected from the group consisting of mineral oils and synthetic poly-alphaolefin oils, and mixtures thereof.

[0061] 13. The composition of aspect 11 or 12, wherein the plasticizer is present in an amount of about 5% to about 60% by weight, preferably about 10% to about 50% by weight, and most preferably about 15% to about 40% by weight, based on the total weight of the composition.

[0062] 14. The composition of any one of aspects 1-13, wherein the composition does not include an amorphous polyalphaolefin.

[0063] 15. The composition of any one of aspects 1-14, wherein the composition does not contain a wax.

[0064] 16. The composition of any one of aspects 1-15, wherein the molecular weight of the high molecular weight propylene copolymer is at least two times, preferably at least three times, and most preferably at least four times the molecular weight of the low molecular weight propylene copolymer.

[0065] 17. The composition of any one of aspects 1-16, wherein the heat of fusion of the low molecular weight propylene copolymer is at least two times, preferably at least three times, and most preferably at least four times, the heat of fusion of the high molecular weight propylene copolymer.

[0066] 18. The composition of any of aspects 1-17, wherein the viscosity of the composition is at most about 17,500 centipoise (cP) at 177°C (350°F), preferably at most about 15,000 centipoise (cP) at 177°C (350°F), and most preferably at most about 12,500 centipoise (cP) at 177°C (350°F).

[0067] 19. The composition of any one of aspects 1-18, further comprising an antioxidant.

[0068] 20. The composition of any one of aspects 1-19, wherein the composition has an elongation at break of at least about 350%, preferably at least about 400%, and most preferably at least about 450%.

[0069] 21. The composition of any one of aspects 1-20, wherein the composition has a yield stress of at least about 0.4 MPa, preferably at least about 0.5 MPa, and most preferably at least about 0.6 MPa.

[0070] 22. The composition of any one of aspects 1-21, wherein the composition has a stress retention of at least 30%, preferably at least about 40%, and most preferably at least about 45%.

[0071] 23. The composition of any of the preceding aspects, wherein the composition has a viscosity that is retained at 177°C by greater than about 90% for at least 3 days, preferably greater than about 95% for at least 3 days, and most preferably greater than about 90% for at least 5 days.

[0072] 24. A method for producing a laminate, comprising: applying the hot melt adhesive composition of any one of Aspects 1 to 23 in a molten state to a primary substrate; and bonding the secondary substrate to the primary substrate by contacting the secondary substrate with the adhesive composition; A method comprising:

[0073] 25. The method of embodiment 24, wherein the primary substrate comprises a first layer of an absorbent core, the secondary substrate comprises a second layer of the absorbent core, and at least one of the first layer or the second layer has a superabsorbent polymer attached thereto.

[0074] 26. An absorbent core comprising a first layer and a second layer, wherein at least one of the first layer and the second layer comprises a superabsorbent polymer, and the first layer and the second layer are adhered to one another by a hot melt adhesive composition according to any one of embodiments 1-23, wherein the adhesive composition adheres the superabsorbent polymer within the absorbent core.

[0075] 27. A disposable hygiene product comprising an absorbent core according to embodiment 26.

[0076] Example The present invention is further illustrated by the following examples. To prepare the hot melt adhesives, all components were weighed into a single-wall aluminum pint can and heated to 177°C under a nitrogen blanket (5 scfh). The aluminum can was loaded with a double-blade impeller in an overhead mixer and stirred at 25 rpm until the polymer was well-moved. The speed was then increased to 50 rpm until the mixture was homogeneous and at a constant temperature. The compounding was considered complete when the mixture appeared homogeneous and no agglomerates from the polymer were visible. This compound was then used to test viscosity, tensile properties, and / or to prepare laminates for final performance testing. The excellent compatibility of the system allowed all components to be mixed together without compromising the overall mixing time. This compatibility and stability created a highly heat-resistant system that was able to maintain viscosity at 177°C for several days.

[0077] Adhesives were made using the ingredients listed below and in Tables 1-3. The number listed for a given ingredient is the weight percent and must equal 100%.

[0078] Calsol 5500 is a naphthenic process oil available from Calumet Specialty Products.

[0079] Indopol H-1900 is a commercially available polyisobutene oligomer with a number average molecular weight of 2,500 g / mol as determined by the supplier (Ineos Capital Ltd) using gel permeation chromatography (GPC), and all references to number average molecular weight of polyisobutenes made herein are based on the same method.

[0080] Indopol H-100 is a commercially available polyisobutene oligomer with a number average molecular weight of 910 g / mol as determined by the supplier (Ineos Capital Ltd) using gel permeation chromatography (GPC).

[0081] Irgafos 168 is tris(2,4-di-tert-butylphenyl) phosphate available from BASF Chemicals and is used as an antioxidant.

[0082] Irganox 1010 is pentaerythritol tetrakis(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate) available from BASF Corp. and is used as an antioxidant.

[0083] Koattro PB M 1200M is a 1-butene copolymer with a density of 0.908 g / cm3 (tested by the supplier in accordance with ISO 1183-1) available from LyondellBasell Industries Holdings.

[0084] Koattro PB M 1500M is a 1-butene copolymer with a density of 0.890 g / cm3 (tested by the supplier in accordance with ISO 1183-1) available from LyondellBasell Industries Holdings.

[0085] Vistamaxx 6502, obtained from ExxonMobil Chemical Company, Houston, TX, contains approximately 13% by weight of ethylene comonomer and has a weight average molecular weight (Mw) of greater than 80,000 g / mol, a molecular weight of 0.865 g / cm 3 The poly(propylene-co-ethylene) is an essentially amorphous poly(propylene-co-ethylene) having a density (reported by the supplier using ASTM D1505) of 1000 MPa.

[0086] Vistamaxx 8380, obtained from ExxonMobil Chemical Company, Houston, TX, is a low molecular weight, low viscosity random propylene-ethylene copolymer. It contains about 12% by weight ethylene comonomer, a weight average molecular weight (Mw) of less than 60,000 g / mol, and a viscosity of 0.864 g / cm. 3 has a density (reported by the supplier) of

[0087] Vistamaxx 8880, obtained from ExxonMobil Chemical Company, Houston, TX, is a semi-crystalline, low molecular weight propylene copolymer consisting of about 6% by weight ethylene comonomer, with a weight average molecular weight (Mw) of less than 60,000 g / mol and a viscosity of 0.879 g / cm 3 has a density (reported by the supplier) of

[0088] Viscosity was measured according to ASTM D3236 with spindle 27 at 163, 177, and 190°C. The spindle speed was adjusted so that the percent torque was between 45% and 90%. The viscosity should be low enough to result in a fiber diameter of 10 to 60 μm when the adhesive was sprayed at 5 gsm using a Nordson Signature™ low flow nozzle.

[0089] Dogbones for tensile testing were made by pouring molten adhesive into a silicone mold, resulting in an overall dogbone length of 3.5" x 1.0" and a thickness of 0.125" when flush with the mold. The test area of ​​the dogbone was 0.5" x 0.5". Excess adhesive was scraped from the silicone mold with a hot spatula so that the dogbone thickness was as close to 0.125" as possible. The samples were allowed to cool to room temperature for at least 12 hours before being tested for elongation to break, maximum stress, and other mechanical tests. The top and bottom of the dogbone were clamped into an Instron tensile tester, leaving only the 0.5" x 0.5" test area exposed. The pull rate was 2" / min and continued until the specimen broke. The elongation at break and maximum stress were automatically calculated in BlueHill3 software available from Instron. The elongation at break was recorded as a percentage based on the difference between the final length and the initial length divided by the initial length to determine if the adhesive could withstand the elongation from swelling of the SAP particles. The goal was to have the adhesive maintain an elongation of approximately 475% or greater. It was also deemed necessary to have good stress retention over time when held at a given elongation. An elongation value of 300%, and an initial test height of 0.5", means that the Instron jaws will extend (at 2" / min) until they are a total of 2" apart. The stress or load value when 300% is reached is recorded. The specimen is then held at 300% elongation for 10 minutes before the final stress or load value is recorded. In the tables below, "% Stress Retained at 300% Elongation, 10 Minutes" refers to the stress after 10 minutes at 300% elongation divided by the initial stress at 300% elongation multiplied by 100, and is therefore listed as a percentage of the stress retained. This factor should be at least 30%, preferably at least about 40%, and most preferably at least about 45% or even at least about 50%.

[0090] Pattern quality was determined qualitatively and quantitatively. The adhesive was heated to approximately 190°C and pumped through a hose into a Signature Low Flow nozzle (Nordson Corp.) at a 5 gsm coat weight and a line speed of 200 ft / min. The air flow was adjusted to produce the most visually fiberized pattern with minimal agglomerates (those with a size greater than approximately twice the average droplet size) or flyaway adhesive strands (qualitative). On average, the air pressure was approximately 20 psi, but this was dependent on the setup of each piece of equipment and is intended only as a reference. The nozzle head was positioned 20 mm above the primary substrate, which was a 33 gsm spunbond nonwoven. The secondary substrate was a release liner, allowing for better sample analysis. Qualitative analysis was performed under a microscope to determine the diameter of the fibers produced during spray application. The goal was to produce fiber diameters of less than 60 μm, preferably less than 30 μm. Since the tensile properties of an adhesive are a function of fiber diameter, the desired fiber diameter can vary depending on the adhesive formulation, desired properties, and other conditions.

[0091] Heat stability was determined by pouring approximately 150 g of adhesive into an 8 oz glass jar and loosely securing the lid. The jar was placed in a high temperature, i.e., 177°C, oven. The jar was removed from the oven daily to observe for charring or gelation, which would indicate incompatibility. Additionally, a 10 g slug of adhesive was poured from the jar daily to determine viscosity retention. Viscosity retention is calculated by dividing the viscosity at a given temperature by the initial viscosity before heat aging and multiplying by 100. Preferably, the viscosity retained is greater than 85% for at least three days. Ideally, the viscosity retained is greater than 90% for at least three days or even at least five days.

[0092] [Table 1]

[0093] Table 1 demonstrates the importance of the polyisobutene (PIB) component and the optional butene-rich polymer. Example 2 shows that the butene-rich copolymer, while optional, is preferred because it reduces the viscosity and increases the elongation and retained stress shown in Example 1. In Comparative Example 1 (CE1), the use of naphthenic oil alone results in an adhesive exhibiting unacceptably low elongation at break, resulting in failure while held at 300% elongation. Inventive Examples 1 and 2, which contain PIB, had elongations to break of greater than 525% and retained more than about 50% of their original stress after 10 minutes at 300% elongation. Example 3, which contains low molecular weight PIB, retained about 35% of the stress after 10 minutes at 300% elongation, with an elongation to break of 463%. All inventive Examples had a maximum stress of at least 0.61 MPa. Furthermore, Examples 1 and 2 desirably yielded an average fiber diameter of 17 μm when 5 gsm was applied at 190°C.

[0094] [Table 2]

[0095] Table 2 demonstrates the role of the high molecular weight propylene copolymer component. Comparative Example 3 (CE3) replaces the high molecular weight component with an additional low molecular weight component. The loss of the high molecular weight component dramatically reduces the elongation to break and completely eliminates the stress retained after 10 minutes at 300% elongation.

[0096] [Table 3]

[0097] Comparative Example 4 (CE4) has a specific gravity of 0.908 g / cm 3 The resulting blends were partially incompatible, exhibiting a rapid decrease in elongation at break and a complete loss of stress retention after 10 minutes at 300% elongation.

[0098] [Table 4]

[0099] Table 4 demonstrates excellent thermal stability through viscosity retention when placed in a 177°C oven for an extended period of time. Ideally, the hot melt adhesive is heated only for the required period of time, but in some cases, it may remain in a molten state for several hours to several days. For example, if a production line is experiencing problems, the adhesive could be held in a molten state until the line is operational again. Furthermore, some manufacturers do not produce product over the weekend and may leave the melt tank open so that they do not have to wait for the adhesive to remelt when the line is restarted. Therefore, it is advantageous to have an adhesive with excellent thermal stability to accommodate these situations. Preferably, the hot melt composition has a viscosity retention at elevated temperatures of greater than about 85% for at least about 3 days, preferably greater than about 90% for at least about 3 days, and most preferably greater than about 90% for at least about 5 days.

[0100] When a range of values ​​is provided, it is understood that each intervening value between the upper and lower limits of that range, and any combination or subcombination of intervening values, and any other stated or intervening value within that stated range, is encompassed within the recited range of values. In addition, the invention includes a range of a component that is the lower limit of a first range and the upper limit of a second range of that component.

[0101] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention belongs. All publications and patents specifically mentioned in this specification are incorporated herein by reference in their entirety for all purposes, including describing and disclosing the chemicals, instruments, statistical analyses, and methods reported in the publications that may be used in connection with the present invention. All references cited herein should be construed as indicating the level of skill in the art. Nothing herein should be construed as an admission that the present invention is not entitled to antedate the disclosure by prior invention.

[0102] Although illustrated and described herein with reference to certain specific embodiments, the invention is nevertheless not intended to be limited to the details shown. Rather, various changes in the details may be made within the scope of the claims and their equivalents without departing from the spirit of the invention.

Claims

1. (a) an essentially amorphous, single-site catalyzed, high molecular weight propylene copolymer; (b) semi-crystalline, single-site catalyzed low molecular weight propylene copolymers; (c) polyisobutene; and (d) polymers of 1-butene based copolymers having a density of at most 0.907 g / cm 3 ; and a tackifier-free hot melt adhesive composition comprising: the high molecular weight propylene copolymer has a weight average molecular weight of at least 80,000 g / mol and a heat of fusion of at most 20 J / g; the low molecular weight propylene copolymer has a weight average molecular weight of up to 60,000 g / mol and a heat of fusion of at least 20 J / g; the high molecular weight propylene copolymer is present in an amount of 10% to 60% by weight, based on the total weight of the composition; the low molecular weight propylene copolymer is present in an amount of from 3 wt.% to 40 wt.%, based on the total weight of the composition; the polyisobutene is present in an amount of 5 wt% to 50 wt%, based on the total weight of the composition; A hot melt adhesive composition, wherein the 1-butene based copolymer is present in an amount of 5% to 40% by weight, based on the total weight of the composition.

2. the high molecular weight propylene copolymer has a weight average molecular weight of at least 95,000 g / mol and a heat of fusion of at most 15 J / g; and 10. The composition of claim 1, wherein the low molecular weight propylene copolymer has a weight average molecular weight of up to 40,000 g / mol and a heat of fusion of at least 25 J / g.

3. The high molecular weight propylene copolymer has a polydispersity index of less than 5; and The composition of claim 1 , wherein the low molecular weight propylene copolymer has a polydispersity index of less than 5.

4. The high molecular weight propylene copolymer is a copolymer of propylene, ethylene and C 4 ~C 12 with a comonomer selected from the group consisting of alkylenes, and The low molecular weight propylene copolymer is a copolymer of propylene, ethylene and C 4 ~C 12 The composition of claim 1 which is a copolymer with a comonomer selected from the group consisting of alkylenes.

5. 10. The composition of claim 1, wherein the polyisobutene has a number average molecular weight of at least 750 g / mole.

6. the high molecular weight propylene copolymer is present in an amount of 20% to 50% by weight based on the total weight of the composition; The low molecular weight propylene copolymer is present in an amount of from 4% to 30% by weight, based on the total weight of the composition; and The composition of claim 1, wherein the polyisobutene is present in an amount of from 10% to 40% by weight, based on the total weight of the composition.

7. The composition of claim 1 , wherein the 1-butene based copolymer comprises a butene-ethylene copolymer.

8. The composition of claim 1, wherein the 1-butene based copolymer has a density of at most 0.905 g / cm3.

9. The composition of claim 1, wherein the 1-butene based copolymer is present in an amount of from 7% by weight to 30% by weight, based on the total weight of the composition.

10. The composition of claim 1 further comprising a plasticizer.

11. 11. The composition of claim 10, wherein the plasticizer is selected from the group consisting of mineral oils and synthetic polyalphaolefin oils and mixtures thereof.

12. The composition of claim 10, wherein the plasticizer is present in an amount of from 5% to 60% by weight based on the total weight of the composition.

13. The composition of claim 1 , wherein the composition is free of amorphous polyalphaolefins.

14. The composition of claim 1 , wherein the composition is free of wax.

15. 2. The composition of claim 1, wherein the molecular weight of the high molecular weight propylene copolymer is at least twice the molecular weight of the low molecular weight propylene copolymer.

16. The composition of claim 1 , wherein the heat of fusion of the low molecular weight propylene copolymer is at least twice as high as the heat of fusion of the high molecular weight propylene copolymer.

17. 10. The composition of claim 1, wherein the composition has a viscosity of up to 17,500 centipoise (cP) at 177°C (350°F).

18. The composition of claim 1 further comprising an antioxidant.

19. The composition of claim 1 , wherein the composition has an elongation at break of at least 350%.

20. The composition of claim 1 , wherein the composition has a yield stress of at least 0.4 MPa.

21. 1. A method for producing a laminate, comprising the steps of: applying the hot melt adhesive composition of any one of claims 1 to 20 in a molten state to a main substrate; and bonding a secondary substrate to a primary substrate by contacting the secondary substrate with the adhesive composition; A method comprising:

22. 22. The method of claim 21, wherein the primary substrate comprises a first layer of an absorbent core and the secondary substrate comprises a second layer of the absorbent core, at least one of the first layer or the second layer having a superabsorbent polymer associated therewith.

23. 21. An absorbent core comprising a first layer and a second layer, at least one of the first layer and the second layer comprising a superabsorbent polymer, the first layer and the second layer being adhered to one another by a hot melt adhesive composition according to any one of claims 1 to 20, the adhesive composition adhering the superabsorbent polymer within the absorbent core.

24. A disposable hygiene article comprising an absorbent core according to claim 23.